2018
DOI: 10.18520/cs/v114/i04/800-807
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Snow Cover in Western and West-Central Himalayas during 2004–2014

Abstract: The extent of snow cover on the earth is considered an important parameter for numerous climatological and hydrological applications. Snow cover dynamics in mountainous regions is a vital input for energy balance, glacier mass balance, climate change and snowmelt runoff modelling. There have been global efforts for monitoring of snow cover of earth at varying spatial and temporal scales by generation of snow products. Among these, one of the high temporal and spatial resolution datasets has been generated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Although patterns vary throughout the Syr Darya and Amu Darya at the subbasin scale, the temperature and precipitation changes generally lead to less snow accumulation as well as an earlier snowmelt, which in combination leads to a shorter annual duration of snow cover (Dedieu et al, 2014;Dietz et al, 2014). Previous work that focused on the northwestern basins could not determine a significant trend in SCA over a 10-year study period (Rathore et al, 2018;Singh et al, 2018); however, in agreement with our 16-year study, other more recent work (Negi et al, 2018) also determined that a decrease in snow cover is occurring over this part of HMA when time periods of at least 15 years are considered. Similarly, when extending the time period even further, from 1986 to 2008, a decline in snow cover was identified above 4,000 m using AVHRR and MODIS data (Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Although patterns vary throughout the Syr Darya and Amu Darya at the subbasin scale, the temperature and precipitation changes generally lead to less snow accumulation as well as an earlier snowmelt, which in combination leads to a shorter annual duration of snow cover (Dedieu et al, 2014;Dietz et al, 2014). Previous work that focused on the northwestern basins could not determine a significant trend in SCA over a 10-year study period (Rathore et al, 2018;Singh et al, 2018); however, in agreement with our 16-year study, other more recent work (Negi et al, 2018) also determined that a decrease in snow cover is occurring over this part of HMA when time periods of at least 15 years are considered. Similarly, when extending the time period even further, from 1986 to 2008, a decline in snow cover was identified above 4,000 m using AVHRR and MODIS data (Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have revealed the influence of the Himalayan snow cover over the Indian monsoonal rainfall and its intensity [22,39,40]. A large portion of this region lies above 4000 m altitude (Figure 1b) and receives snow throughout the year [41]. Rivers originating from the higher Himalaya such as Ganga, Satluj, and Chenab, receive about 30-50% of the annual flow from its snowmelt runoff [7,42].…”
Section: Study Areamentioning
confidence: 99%
“…Rivers originating from the higher Himalaya such as Ganga, Satluj, and Chenab, receive about 30-50% of the annual flow from its snowmelt runoff [7,42]. Major rivers and their tributaries originating from the northwest Himalaya (NWH) are key elements of agriculture systems, ecology, hydropower, and numerous socioeconomic and cultural developments in the Indian subcontinent [41,43]. The region receives snow generally from November to March, while snowmelt from April to June provides the predominant runoff source, which forms a significant constituent besides precipitation during the monsoon time [7,28].…”
Section: Study Areamentioning
confidence: 99%
“…In addition to ice-related processes, snow cover has significant spatial and temporal variations over the Himalaya. Snow cover is regulated by seasons, topography, and hydrometeorology (Singh et al, 2014;Gurung et al, 2017;Rathore et al, 2018). Different techniques were proposed to estimate snow cover over different regions.…”
Section: Snow Cover Snow Depth and Snow Water Equivalent Variability ...mentioning
confidence: 99%